First azole‐resistant Aspergillus fumigatus isolates with the environmental TR46/Y121F/T289A mutation in Iran. Issue 5 (13th March 2020) - Ahangarkani, Fatemeh; Puts, Ynze; Nabili, Mojtaba; Khodavaisy, Sadegh; Moazeni, Maryam; Salehi, Zahra; Laal Kargar, Melika; Badali, Hamid; Meis, Jacques F.
Summary: Background: Azole resistance in Aspergillus fumigatus is an emerging problem and reported from all continents. As triazole antifungals are the mainstay of therapy in the management of invasive aspergillosis, azole‐resistant A fumigatus has become a major medical concern and with complicated clinical management. Objective: Screening of environmental presence of azole‐resistant A fumigatus in Iran. Methods: Compost from Northern Iran, collected between 2017 and 2018, was screened for the presence of azole‐resistant A fumigatus with azole‐containing agar. Phenotypic MICs were obtained from selected, molecularly confirmed isolates. cyp51A gene sequencing and genotyping of azole‐resistant isolates were done. Results: Among 300 compost samples, three A fumigatus isolates had high voriconazole MICs (≥16 mg/L) and harboured the TR46 /Y121F/T289A mutation in the cyp51A gene. Microsatellite typing of these isolates showed that two strains had the same allele across all nine examined microsatellite loci and were genotypically related to Indian azole‐resistant strains. The other isolate had a different genotype. Conclusion: This is the first report of A fumigatus with TR46 /Y121F/T289A mutation from the region. Monitoring and surveillance of antifungal susceptibility of clinical A fumigatus is warranted in Iran and elsewhere in the region.